2022
DOI: 10.3389/fpubh.2021.754681
|View full text |Cite
|
Sign up to set email alerts
|

Widowhood and Life Satisfaction Among Chinese Elderly Adults: The Influences of Lifestyles and Number of Children

Abstract: Our study examined how lifestyle and number of children influence the relationship between widowhood and life satisfaction based on self-regulation theory. A sample of 2,968 elderly respondents (male = 1,515, female = 1,453, mean age = 69.12 years, SD = 7.24) participated in Chinese General Social Survey. Our findings suggest that lifestyle is positively related to life satisfaction, and number of children is positively associated with life satisfaction but negatively related to lifestyle. The moderated mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Widowed elderly individuals who have children were found to be more likely to show higher level of satisfaction with life. 3 A result from a nationwide cohort study showed that having children was associated with a longer survival after hip fracture. The authors suggested that adult children may support their ageing parents with hip fracture, thereby potentially increasing survival chances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Widowed elderly individuals who have children were found to be more likely to show higher level of satisfaction with life. 3 A result from a nationwide cohort study showed that having children was associated with a longer survival after hip fracture. The authors suggested that adult children may support their ageing parents with hip fracture, thereby potentially increasing survival chances.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 This also implies that social and familiar support, especially their adult children, may be important to improve prognosis. 3 , 36 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim is to investigate and comprehensively evaluate the health status and related factors of the widowed elderly in China, so as to make targeted health promotion measures to reduce the negative impact of widowhood on the elderly and their families. According to previous research, the factors affecting the health of the widowed elderly can be roughly divided into natural attributes [15], lifestyle [16], social characteristics [17], socio-economic status [18], prevalence of disease [19] and psychological factors [20]. Thus, based on previous studies and the questionnaire of the Chinese Longitudinal Healthy Longevity Survey in 2018 (CLHLS-2018), the current study investigates the impact of 11 factors (hearing difficulties, sleeping, falling, life restriction, physical exercise, social activities, endurance insurance, type of elderly care, chronic diseases, life satisfaction and negative symptoms) on the health of the widowed elderly from the six aspects of lifestyle, socio-economic status, social characteristics, prevalence of disease and psychological factors.…”
Section: Introductionmentioning
confidence: 99%